Implementing Self-Defense Training and Legal Assistance to Prevent Sexual Violence in Pesantren Environments - Rahmawati, Titik; Syaroni, Mokh; Salim, Zuraida Febriani; Nada, Ella Izzatin (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2023)
Islamic boarding schools (pesantren) are crucial environments that should ensure the safety and well-being of their students. However, reports of sexual violence incidents involving students, particularly perpetrated by teachers or educators within the pesantren, have raised serious concerns. This community service initiative aims to mitigate such issues through a program focused on self-defense training and legal support. Implemented using the ABCD (Asset Based Community Development) method, the program involved 30 male and female students from Pondok Pesantren Usysyaqul Qur’an Kendal. Evaluation of the program's impact revealed significant outcomes: 95% achievement of training objectives, 98% achievement of material delivery targets, an 87% improvement in students' understanding of sexual violence issues, and 90% satisfaction among students regarding the program's effectiveness and enjoyment. These results underscore the program's success in enhancing students' awareness and preparedness concerning sexual violence prevention in pesantren settings.